T-Shaped Palladium and Platinum {MNO}10 Nitrosyl Complexes - Sinclair, Matthew J.G.; Roig, Nil; Gyton, Matthew R.; Tsoureas, Nikolaos; Cloke, F. Geoffrey N.; Alonso, Mercedes; Chaplin, Adrian B. (Inorganic Chemistry, 2024)
The synthesis and characterization of a homologous series of T-shaped {MNO}10 nitrosyl complexes of the form [M(PR3)2(NO)]+ (M = Pd, Pt; R = tBu, Ad) are reported. These diamagnetic nitrosyls are obtained from monovalent or zerovalent precursors by treatment with NO and NO+, respectively, and are notable for distinctly bent M-NO angles of ∼123° in the solid state. Adoption of this coordination mode in solution is also supported by the analysis of isotopically enriched samples by 15N NMR spectroscopy. Effective oxidation states of M0/NO+ are calculated, and metal-nitrosyl bonding has been interrogated using DFT-based energy decomposition analysis techniques. While a linear nitrosyl coordination mode was found to be electronically preferred, the M-NO and P-M-P angles are inversely correlated to the extent that binding in this manner is prevented by steric repulsion between the bulky ancillary phosphine ligands.